2009
DOI: 10.1002/jbm.a.32231
|View full text |Cite
|
Sign up to set email alerts
|

Processing of type I collagen gels using nonenzymatic glycation

Abstract: This study focuses on the development of a novel method of non-enzymatic glycation of fibrillar collagen gels. In contrast to previous studies in which type I collagen gels were glycated in the solid state, this study presents a method for glycation in solution. Type I collagen in solution or gels was exposed to a range of ribose concentrations from 0–250mM. The binding of ribose to collagen was documented using Fourier Transform Infrared (FTIR) Spectroscopy. Formation of advanced glycation endproducts (AGEs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
118
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(132 citation statements)
references
References 71 publications
12
118
2
Order By: Relevance
“…Previously it has been shown that exposure to ribose in solution glycates type I collagen scaffolds resulting in ribose attachment measured by FTIR, AGE accumulation measured by fluorescence, and increased mechanical properties over control gels. 31,36 Given this data, another possible mechanism for augmentation of matrix retention is that glycation lowers the pore size in the collagen gels hindering diffusion of macromolecules out of the constructs. This could be particularly advantageous or beneficial in tissue engineering techniques, where the production and retention of matrix is extremely important to construct functionality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously it has been shown that exposure to ribose in solution glycates type I collagen scaffolds resulting in ribose attachment measured by FTIR, AGE accumulation measured by fluorescence, and increased mechanical properties over control gels. 31,36 Given this data, another possible mechanism for augmentation of matrix retention is that glycation lowers the pore size in the collagen gels hindering diffusion of macromolecules out of the constructs. This could be particularly advantageous or beneficial in tissue engineering techniques, where the production and retention of matrix is extremely important to construct functionality.…”
Section: Discussionmentioning
confidence: 99%
“…A stock solution of 500 mM ribose in 0.1% acetic acid was used to glycate the collagen in solution (pre-glycation) with final concentrations of 250 mM ribose and 1.5 mg/mL collagen at 48C for 5 days prior to gelation. 31,36 Ribose (250 mM) dissolved in low glucose DMEM with 10% FBS, 100 units/mL penicillin, 100 mg/mL streptomycin, and 25 ng/mL amphotericin B was used to glycate 1.5 mg/mL collagen gels at 378C (post-glycation) for 5 days. 31,36 It is important to note that cells were present during in the post-glycated processing method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Type I collagen gels were prepared as reported elsewhere [22]. Type I collagen solution (4 mg/ml in 20 mM acetic acid) was diluted, on ice, with 0.1% acetic acid and neutralized with 0.4 M NaOH (pH 10.2) in PBS buffer to form 1.5 mg/ml gels.…”
Section: In Vitro Glycation Of Type I Collagenmentioning
confidence: 99%
“…10 In a recent study, the ratio of the integrated absorbance of the carbohydrate region to the amide I absorbance was used to study the differences in AGEs between control and ribosetreated articular cartilage samples. 13 In the present study, the maximum correlation coefficient between the Pent concentration and the variables in the carbohydrate region was r ¼ 0.50.…”
Section: Discussionmentioning
confidence: 99%